The Influence of Oxygen Substitution on the Optoelectronic Properties of ZnTe - Imad Khan; Sajid Khan; Javid Iqbal; H. A. Rahnamaye Aliabad; Zahid Ali; Iftikhar Ahmad (Journal of Chemistry)
We communicate theoretical results of the structural, electronic, and optical properties of ZnOxTe1-x (0≤x≤1) in the zincblende structure. The calculations are performed using full potential linearized augmented plane waves (FP-LAPW) method, based on density functional theory (DFT). The structural properties are calculated with simple GGA (PBEsol), while the electronic and optical properties are calculated using mBJ-GGA. The mBJ-GGA is used to properly treat the active d-orbital in their valence shell. The ZnOTe alloy is highly lattice mismatched and consequently the lattice constants and bulk moduli largely deviate from the linear behavior. The calculated bandgaps are in agreement with the experimentally measured values, where the nature of bandgaps is direct for the whole range of x except at x=0.25. We also calculate the bandgap bowing parameter from our accurate bandgaps and resolve the existing controversy in this parameter.